2014
DOI: 10.1186/1746-160x-10-52
|View full text |Cite|
|
Sign up to set email alerts
|

Use of porous high-density polyethylene grafts in open rhinoplasty: no infectious complication seen in spreader and dorsal grafts

Abstract: ObjectiveThe aim of this study is to use porous high-density polyethylene grafts (Medpor) in open rhinoplasty and then assess complication rate and aesthetic outcomes.MethodsIn a prospective cohort study, we performed open rhinoplasty and employed Medpor as rhinoplasty grafts. Then we compared their complication rate.ResultsIn a total of 64 patients, 84 Medpor grafts -38 dorsal grafts, 23 strut grafts, 8 rim grafts, 5 button grafts and 10 spreader grafts – were utilized. Moreover, 5septal perforation repairs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Mohammadi et al [7] showed that minimum complications were low when Medpor implants were used as dorsal and, especially, spreader grafts, but most of the infectious complications and extrusion were observed after implanting Medpor as a strut and rim graft. They recommend the safe use of Medpor implants only as spreader graft.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mohammadi et al [7] showed that minimum complications were low when Medpor implants were used as dorsal and, especially, spreader grafts, but most of the infectious complications and extrusion were observed after implanting Medpor as a strut and rim graft. They recommend the safe use of Medpor implants only as spreader graft.…”
Section: Discussionmentioning
confidence: 99%
“…Other autogenous materials such as costal and conchal cartilages offer a bountiful supply of cartilage and can provide structural support but are associated with donor site morbidity. In a recent clinical research, Medpor was shown to be a useful dorsal and spreader graft in reconstruction of severe nose deformities, with the lowest complication rate and without infectious complications and extrusion [6][7][8][9][10]. Thus, building a midline framework with Medpor to extend the septum will provide a strong support to the caudal part of the implant and autogenous cartilage grafts on the tip.…”
Section: Introductionmentioning
confidence: 99%
“…Medpor ® can be used as columellar strut, dorsal, spreader, rim and batten grafts and in patients with septal perforation. The complications cited are lateral movement of implant, fistula formation, skin thickness, erythema, abscess formation, extrusion of the implant (inserting it close to the incision site is a risk factor for extrusion) and infection 19 .…”
Section: Medpor ® (High-density Polyethylene)mentioning
confidence: 99%
“…Another contraindication of this implant is the strut grafts. It can be used as dorsal and spreader grafts and for small-size septal perforations 19 .…”
Section: Medpor ® (High-density Polyethylene)mentioning
confidence: 99%
“…The most frequent complications quoted in the relevant literature regarding this type of mesh are: lateral displacement of the implant, fistula or abscess formation, implant extrusion and infection. [1,22]. Medpor is used for malar and chin augmentation [23].…”
Section: Alloplastic Materialsmentioning
confidence: 99%